PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PROFITABILITAS (Pada perusahaan Syariah Sektor Manufaktur Yang terdafar di Indeks Saham Syariah Indonesia) - Sukri, Dina Ranvica; Faturahman , Faturahman; Rahma, Sri; Anita, Efni (Manajemen Keuangan Syariah, 2024)
This research was conducted with the aim of examining the influence of company size, leverage and company growth on profitability in manufacturing sector companies listed on the Indonesian Sharia Stock Index for 2018-2022. This research was tested using 3 independent variables, namely: company size, leverage and company growth, for the dependent variable, namely profitability. The population used in this research is manufacturing sector companies listed on the 2018-2022 Indonesian Sharia Stock Index. There were 70 samples in this research, and used multiple linear analysis assisted by the Eviews 12 data analysis tool in this research, namely panel data. There are results, namely that company size has a partial positive and significant effect on profitability, leverage has a positive and significant effect on profitability, while company growth has a partial negative effect on profitability. Simultaneous test results of company size, leverage and company growth have an influence on profitability. Â